IMPROVED RELIABILITY OF OPERATION OF GAS SUPPLY SYSTEMS ON THE BASIS OF SERVICE OPTIMIZATION - Grudz, V. Y.; Grudz, Y. V.; Bodnar, V. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2018)
General principles of the spare parts amount selection when operating gas supply systems for renewable and non-renewable elements have been developed. Nomenclature is considered as a list of numbers and names of reserve instruments and equipment, which is compiled in accordance with a certain grouping and sequencing according to the producing plants technical documentation and which includes mechanical details, assemblies, and aggregates. The assessment criteria of the spare parts set sufficiency have been chosen based on the condition of the sufficient system operation reliability which is based on the estimates of the failure emergence probability during the period of regular element removals. The demand for spare parts and materials is of random nature and it is considered as a stable process which is described by the Poisson’s distribution. The calculation principle comes down to determining the possibility of the fact that all the service channels and waiting spaces in the mechanism will be filled in accordance with the queuing theory. The technique for spare parts amount selection when operating gas supply systems has been developed eventually.